Reflectance confocal microscopy for the noninvasive diagnosis of cutaneous juvenile xanthogranuloma. Issue 1 (18th July 2018) - Pimenta, R.; Leal‐Filipe, P.; Oliveira, A.
Abstract: Juvenile xanthogranuloma is the most common type of non‐Langerhans cell histiocytosis. It appears primarily in infancy, where its differential diagnosis includes Spitz nevus, dermal nevus and molluscum contagiosum. We report the case of a 2‐year‐old boy with juvenile xanthogranuloma, as diagnosed using real‐time, in vivo reflectance confocal microscopy.